Regulatory Frameworks to Integrate Corporate Social Responsibility with Circular Economy Principles - Sunaryo, Sunaryo; Kasmawati, Kasmawati; Pham, Hong Nhung; Rahayu, Astri (Hasanuddin Law Review, 2025)
The urgency of integrating environmental Corporate Social Responsibility (CSR) and circular economy principles into legal policy frameworks has become increasingly critical in the energy transition era. This study examines the regulatory challenges hindering the alignment between CSR obligations and circular economy objectives in Indonesia, particularly the legal disconnection between Law No. 40 of 2007 on Limited Liability Companies and broader environmental regulations. Utilizing a normative legal research method, the study analyzes statutory instruments, policy documents, and international legal frameworks to assess the coherence and efficacy of existing laws. Findings reveal that CSR implementation remains fragmented and often symbolic, while circular economy practices lack regulatory incentives and enforcement, especially in resource-intensive sectors. This gap not only undermines sustainability efforts but also delays the shift toward a low-carbon economic model. The study underscores the need for regulatory harmonization, including revising corporate and environmental laws to embed circular economy principles into CSR obligations. The novelty of this research lies in offering an integrative legal perspective that bridges CSR and circular economy concepts, presenting a policy blueprint to accelerate Indonesia's transition toward a more sustainable and environmentally accountable corporate ecosystem.